2019
DOI: 10.1038/s41598-019-47329-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Echinacea purpurea leaf microbiota on chicoric acid level

Abstract: The controversial anti-proliferative effects of Echinacea purpurea (L.) Moench (Asteraceae) might be related to different plant metabolites contained in plant samples, extracts and products. The influence of bacterial endophytes on the synthesis of bioactive compounds in the medicinal plants has been previously demonstrated but there are only few studies addressing anticancer effects and mechanisms of E . purpurea extracts following endophyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Another study suggested that Echinacea purpurea is an excellent model for studying medicinal plant–microbiome interactions ( Maggini et al, 2020 ). The E. purpurea microbiome (bacterial strains isolated from stems and leaves) interaction model showed that microbiome can affect the production of VOCs, phenylpropanoid, and alkamides in the plants ( Maggini et al, 2017 , 2019a , b ).…”
Section: Plant Microbiomes Contribute To the Productions Of Psmsmentioning
confidence: 99%
“…Another study suggested that Echinacea purpurea is an excellent model for studying medicinal plant–microbiome interactions ( Maggini et al, 2020 ). The E. purpurea microbiome (bacterial strains isolated from stems and leaves) interaction model showed that microbiome can affect the production of VOCs, phenylpropanoid, and alkamides in the plants ( Maggini et al, 2017 , 2019a , b ).…”
Section: Plant Microbiomes Contribute To the Productions Of Psmsmentioning
confidence: 99%
“…From the point of view 2 of 17 of medical and pharmaceutical applications, alginates are very promising, because they belong to biocompatible and biodegradable components. In our research, we used alginates, which constitute linear polymers composed of (1→4)-α-L-guluronic acid blocks (GG), (1→4)-β-D-mannuronic acid blocks (MM) and, additionally, heteropolymeric sequences of M and G (MG blocks) [11,12]. Moreover, in the case of the preparation of hydrogel or composite materials, alginates are used together with some additional polymers, such as: poly acrylamide (PAAm) [13], poly(acrylic acid) (PAA) [14], gelatin [15], and chitosan [16], as well as PVA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Echinacea purpurea contains many active substances, such as polysaccharides, caffeic acid derivatives (including cichoric acid), alkylamides, and glycoproteins [10,11]. The most active compounds of Echinacea purpurea are polyphenols-derivatives of caffeic acid: caftaric acid, chlorogenic acid, cynarin and silicic acid [12]. They play a significant role in the therapeutic effect of this plant, especially in activating the immune system by triggering the alternating complement pathway, as well as increasing the number of white blood cells distribution, stimulating phagocytosis, T-cell production, lymphocytic activity, cytokine production, cell respiration and enzyme secretion [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, concerning bacterial microbiota associated with MPs, the comprehension of the forces driving the composition and structure of such microbial population(s) acquires even higher importance since it has been demonstrated that the plant microbiota plays a relevant role in the production of the plant secondary metabolites with therapeutic effects. As cited above, for example, the plant-endophyte interaction strongly acts on the secondary metabolism of E. purpurea [13,14].…”
Section: Mps Bacterial Endophytesmentioning
confidence: 94%
“…Echinacea is a medicinal plant used in therapy and prevention of infectious diseases of the upper respiratory tract, also recently studied for the presence of bacterial endophytes influencing the biosynthesis of alkamides and caffeic acid derivatives [13,14]. The combined use of Echinacea with azithromycin has produced favorable outcomes in comparison to the use of azithromycin alone in pediatric patients with recurrent tonsillitis [15].…”
Section: Mps and Antimicrobial Powermentioning
confidence: 99%